Tibetan Precious Pills as Therapeutics and Rejuvenating Longevity Tonics - Gerke, Barbara (History of Science in South Asia)

(untitled) (University of Alberta Library, 2017)
Tibetan precious pills are frequently attributed with a variety of efficacies, from “magical” powers, prevention of poisoning and infectious diseases, protection from harmful spirits and exposure to diseases while travelling, to rejuvenating and prolonging life through clearing the senses and promoting strength and vigor. They are prescribed as strong medicines for severe diseases, but are also advertised as rejuvenating tonics for the healthy. This paper explores the rejuvenating qualities attributed to precious pills in terms of how they are currently advertised, how rejuvenation is and has been explained in Tibetan works on precious pills, and how Tibetan physicians understand these attributes. How do these domains interact and refer to each other?I compare aspects of rejuvenation in precious pill formulas with contemporary presentations of precious pills online and on published leaflets given out to patients in India and elsewhere. In Tibetan medical texts certain precious pills that contain the complex and processed mercury-sulfide ash called tsotel in addition to a large variety of other medicinal substances are presented as “precious pills” or rinchen rilbu, and only some of those are said to have rejuvenating effects on the body; most are primarily prescribed for specific diseases. The practice of giving precious pills to the healthy emerges more prominently in eighteenth to nineteenth century manuals on administering precious pills (Czaja 2015), which parallels the establishment of influential medical and monastic networks that promoted the making of tsotel and precious pills. I argue that precious pills have more recently widened their specific therapeutic target beyond that of medicine into becoming popular pills for rejuvenation, even if they do not contain tsotel, as part of pharmaceutical commodification. I also show how presentations of precious pills as “rejuvenating” are deeply linked to their availability.